Wound healing activity of lectin isolated from seeds of Centrolobium microchaete Mart. ex Benth. on cutaneous wounds in mice. Issue 18 (8th September 2022) - do Nascimento Neto, Luiz Gonzaga; Vasconcelos, Mayron Alves de; Pinheiro, Aryane de Azevedo; Ramos, Ana Patrícia Magalhães; Silva, Renally Barbosa da; Andrade, Alexandre Lopes; Arruda, Francisco Vassiliepe Sousa; Queiroz, José Ajax Nogueira; Teixeira, Edson Holanda
Abstract: This study aims to evaluate the wound healing potential of lectin isolated from the seeds of Centrolobium microchaete (Mart. ex Benth) (CML) on cutaneous wounds in mice. CML did not show cytotoxicity on murine dermal fibroblasts (L929 cell line). The wounds treated with CML (200 μg/mL) showed a decrease in area within 12 days post-operative (P.O.) when compared to control. On 3 rd and 7 th day P.O., the CML-treated group exhibited fibroblast proliferation and neovascularization. On 12 th day P.O., complete restructuring of the epithelial layer and connective tissue was observed in the CML-treated group, whereas control groups exhibited incomplete reepithelialization. CML treatment enhanced the wound closure via the wound contraction process, resulting in the restructuring of the skin layers on 12 th day P.O. In conclusion, CML induced a fast and efficient wound healing, suggesting that it can be used as a promising therapeutic tool to heal acute wounds. Graphical Abstract: UF0001